TGF-β1 induces epithelial-to-mesenchymal transition via inhibiting mitochondrial functions in A549 cells. (2nd December 2018) - Zhang, Jiaxin; Zhang, Wei; Zhang, Tao; Zhou, Qingbiao; Liu, Jiangzheng; Liu, Ying; Kong, Deqin; Yu, Weihua; Liu, Rui; Hai, Chunxu
Abstract: Epithelial-to-mesenchymal transition (EMT) is critical to the progression of several disease processes including carcinoma metastasis and organ fibrosis. Recent studies show that reactive oxygen species (ROS) and mitochondrial dysfunction have been associated with EMT. However, the role of mitochondria in the EMT process remains to be elucidated. Through the induction of EMT using TGF-β1, we demonstrated that mitochondrial functions were abnormal by increasing ROS production and reducing mitochondrial membrane potential, ATP content and mitochondrial complex protein expression. Resveratrol, a mitochondria protective agent, was found to prevent EMT by preserving mitochondrial functions during the process. However, the inhibitory effects of resveratrol on EMT were abolished in mitochondrial DNA-depleted cells. These findings suggest a critical role for mitochondria in EMT and implicate the protection of mitochondria as a potential target to prevent EMT to treat tumour metastasis or tissue fibrosis, and other diseases involving with mitochondria.